The role of pawnshops in the loan market: Ukrainian and foreign experience - Shkvarchuk, Liudmyla; Vitalii, Hamalii (Видавництво Львівської політехніки, 2013)
In this paper the current state of pawnshops activity in the Ukrainian loan market is analyzed. This paper defines advantages and disadvantages of pawnshop loans compared to other short-term loans, and provides a comparative analysis of the pawnshop industries in Ukraine, Sweden and the USA.
Keywords: pawnshop; secured loan; consumer credit; microcredit; short-term loan; mortgage assets; pawnbroking services